Transnational and Transdisciplinary Lessons of COVID 19 From the Perspective of Risk and Management - Baker, Julien S.; Gao, Yang; Cole, Alistair; Tran, Emilie; Yue, Xiao-Guang (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Rarely has scientific research been as solicited as societies struggle to cope with the coronavirus. The questions raised by COVID-19 are germane to the medical and the social sciences. From an international relations perspective, COVID-19 gets to the heart of what comprises the global commons. From a public policy perspective, COVID-19 is the wicked policy problem par excellence, requiring inter-agency collaboration. From a comparative politics perspective, COVID-19 provides a vast living dataset to engage in multi-level comparisons and real-time experiments. In the medical research field, the pandemic has provided advancements in medical science that would not have been possible without access to a living laboratory. The reprint addresses the transnational and transdisciplinary challenges posed by the COVID-19 pandemic. Responding to existential dilemmas, the COVID-19 pandemic calls for a major transdisciplinary research effort that necessarily combines several levels of empirical analysis and methodological tools and bridges distinct academic and scientific traditions. The main sections of the reprint provide specific insights from medical and social sciences, health and well-being, politics and society and international relations. Though the chapters are framed in terms of distinct disciplinary perspectives and traditions, the overarching spirit of the book to open up received wisdoms and paradigms to challenges from scholars working in different academic disciplines and traditions.